Assessment of different organic substrates for Bio-Electricity and Bio-Hydrogen generation in an Integrated Bio-Electrochemical System. (2023) - Gautam, Rahul; Nayak, Jagdeep K.; Talapatra, K. Namita; Amit,; Ghosh, Uttam Kumar
Abstract: The population explosion and exponential increase in energy demand of the world have created enormous stress on finite fossil fuels and posed a threat to the environment. The sustainable Bio-Electrochemical Systems which include Microbial Fuel Cells (MFC), Microbial Electrolysis Cells (MEC) etc. can generate energy from waste. The present study has intended to utilize Sewage sludge (SS), Compost leachate (CL), and Mess Food waste (FW) as an organic substrate in an Integrated Bio-Electrochemical system to evaluate the bioelectricity generation potential in dual-chambered H type MFCs, then utilization of digestate from MFCs for Bio-hydrogen production in MECs. The maximum open-circuit voltages of 595 mV, 505 mV, and 690 mV were recorded in SS, CL, and FW fed MFC respectively, and their corresponding peak power densities of 1.8 ± 0.1 W/m2, 1.3 ± 0.1 W/m 2 and 2.4 ± 0.1 W/m 2 respectively were generated. The COD removal of 62.37%, 66.8%, and 50.19% were achieved for MFC fed with SS, CL, and FW respectively. The digestate fed MECs had further shown COD removal of 55.26%, 64.40% and 46.61% of the digestate in the "MFC turned MEC" system. The corresponding volumes of gas produced per gram of COD removal were reported as 23.8, 18.1 and 55.1 for SS, CL and FW respectively. The overall COD removal by bio-electrochemical system (BES) of 83.25%, 88.23 % and 73.41% for SS, CL and FW were achieved. The higher OCV of 690 mV and 55.1 mL of bio-hydrogen per gram of the COD removed has suggested the suitability of the FW for Integrated Biochemical system. . The comparative higher performance of FW as feeds has established itself as a potent choice for bio-electricity and bio-hydrogen production.